2022
DOI: 10.3390/plants11091237
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analyses of MADS-Box Genes in Humulus lupulus L. Reveal Potential Participation in Plant Development, Floral Architecture, and Lupulin Gland Metabolism

Abstract: MADS-box transcription factors (TFs) are involved in multiple plant development processes and are most known during the reproductive transition and floral organ development. Very few genes have been characterized in the genome of Humulus lupulus L. (Cannabaceae), an important crop for the pharmaceutical and beverage industries. The MADS-box family has not been studied in this species yet. We identified 65 MADS-box genes in the hop genome, of which 29 encode type-II TFs (27 of subgroup MIKCC and 2 MIKC*) and 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 81 publications
1
11
0
Order By: Relevance
“…Gray ex Hook (105 genes) ( Leseberg et al, 2006 ). Interestingly, the size of MADS-box TF family identified in H. lupulus (65) ( Gutierrez et al, 2022 ) is very close to the numbers of EuMADS TFs we found here. Neither male nor female flowers in E. ulmoides comprise sepal and petal, only have bracts encompassing 8–12 stamens (male) or one pistil (female) ( Wang et al, 2020 ).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Gray ex Hook (105 genes) ( Leseberg et al, 2006 ). Interestingly, the size of MADS-box TF family identified in H. lupulus (65) ( Gutierrez et al, 2022 ) is very close to the numbers of EuMADS TFs we found here. Neither male nor female flowers in E. ulmoides comprise sepal and petal, only have bracts encompassing 8–12 stamens (male) or one pistil (female) ( Wang et al, 2020 ).…”
Section: Discussionsupporting
confidence: 84%
“…The MADS-box TF family has been studied in certain species with bisexual flowers, e.g., tomato (137 genes) ( Wang et al, 2019 ), foxtail millet (89 genes) ( Lai et al, 2022 ) and American beautyberry (78 genes) ( Alhindi and Al-Abdallat, 2021 ), and a few species with unisexual flowers, such as litchi ( L. chinensis , 101 genes) ( Guan et al, 2021 ), hop ( H. lupulus L., 65 genes) ( Gutierrez et al, 2022 ) and Populus trichocarpa Torr. & A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cucumber genome (ChineseLong_genome_v3) was downloaded from the CuGenDB ( , accessed on 18 June 2022). The hidden Markov model (HMM) of the DUF966 domain (PF06136) was downloaded from Pfam ( , accessed on 18 June 2022) and used as query sequences to perform first-round BLASTp against cucumber reference protein sequences (e-value < 10 −10 ) [ 33 ]. The reported DUF966 protein sequences were collected and used as query sequences to perform the second round of BLASTp [ 2 ].…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, all MADS-box proteins share the conserved MADS-box domain of around 60 amino acids in the N-terminus (also known as the M domain). Among them, MIKC-type genes encode plant-specific MADS-box proteins due to the presence of three additional domains (the intervening domain, keratin domain, and C-terminal domain) [ 17 ]. Two subtypes of MIKC, MIKC C , and MIKC*, have been recognized based on variances in the intervening domain [ 18 ].…”
Section: Introductionmentioning
confidence: 99%